Loppukäyttäjien haasteet Salesforce CRM -järjestelmän käyttöönotossa - Korpi, Samuli (2024)
The purpose of this study was to determine, through the experiences of project managers, what difficulties end users encountered during Salesforce implementation projects. Project managers often face various challenges in their projects, which can be related to both technical and human factors, such as personnel training and resistance to change. Salesforce is one of the leading CRM systems on the market, and its versatility allows customization to meet the needs of different organisations, but it also brings significant challenges for project management. The study used qualitative methods and consisted of a literature review and an empirical part. The literature review examined previous studies and theories on CRM systems, cloud service implementation, and project management. The empirical part involved thematic interviews that enabled the collection of in-depth information on end-users' experiences and perspectives. The interview data were analysed using content analysis to identify key themes and findings. The results of the study showed that end-users' technical skills, motivation, and participation in the various phases of the project are critical factors for successful system implementation. End-user engagement and active participation during the project are decisive factors in the adoption of new technologies. The study also highlighted the importance of effective change management and communication. It is essential for organisations to provide ongoing support and training to end-users to help them enhance their skills in using the system. This includes regular updates to the system and training sessions to keep end-users informed about the latest features and best practices. Additionally, actively listening to end-user feedback is a crucial part of the implementation process, enabling project teams to continually improve and adapt the system to better meet user needs. Based on the study, organisations and project managers could develop better project management practices that support end-users' motivation, learning, and commitment to adopting new technologies. Particularly, the need to develop user-centred training methods and change management models emerged as key areas for improvement.